(untitled) (PANGEEA, 2025)
ABSTRACT: The global business environment is changing rapidly and organisations that adapt to change are the ones that will survive. Organisations need to develop strategies to withstand these changes. Those that are able to survive will be able to resist more than others. One of the biggest challenges facing organisations today is how to manage workforce turnover, which can be caused by the migration of many industrial workers. This may be due to their lack of motivation and commitment to the organization; this view emphasizes the importance of studying Motivation and its relationship with job satisfaction (Tiwari, 2011, p.33). Starting from Dwight D. Eisenhower’s statement, Motivation is the art of getting people to do what you want them to do because they want to do it, and analyzing it in depth, we conclude that motivation, the power to influence people and their actions, is an art that advertises quality.